2022
DOI: 10.1161/hypertensionaha.121.18921
|View full text |Cite
|
Sign up to set email alerts
|

Higher Arm Versus Lower Arm Systolic Blood Pressure and Cardiovascular Outcomes: a Meta-Analysis of Individual Participant Data From the INTERPRESS-IPD Collaboration

Abstract: Background: Guidelines recommend measuring blood pressure (BP) in both arms, adopting the higher arm readings for diagnosis and management. Data to support this recommendation are lacking. We evaluated associations of higher and lower arm systolic BPs with diagnostic and treatment thresholds, and prognosis in hypertension, using data from the Inter-arm Blood Pressure Difference—Individual Participant Data Collaboration. Methods: One-stage multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Recent evidence showed that concordance of the higher BP arm‐side was 63% overall, rising to 73% and 92% when the mean IAD was equal to or higher than 5 and 10 mmHg, respectively. This confirms consistency of IADs, especially where the average IAD was equal to or higher than 10 mmHg 28 . In addition, Clark and associates found in their meta‐analysis that an IAD of 10 mmHg or more was associated with peripheral vascular disease.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Recent evidence showed that concordance of the higher BP arm‐side was 63% overall, rising to 73% and 92% when the mean IAD was equal to or higher than 5 and 10 mmHg, respectively. This confirms consistency of IADs, especially where the average IAD was equal to or higher than 10 mmHg 28 . In addition, Clark and associates found in their meta‐analysis that an IAD of 10 mmHg or more was associated with peripheral vascular disease.…”
Section: Discussionsupporting
confidence: 63%
“…This confirms consistency of IADs, especially where the average IAD was equal to or higher than 10 mmHg. 28 In addition, Clark and associates found in their meta-analysis that an IAD of 10 mmHg or more was associated with peripheral vascular disease. This finding was based on 20 studies of which the majority did not use the consistency method.…”
Section: Strengths and Limitations Of The Approachmentioning
confidence: 99%
See 3 more Smart Citations